The Importance of Nutritional Intake and Nutritional Status to the Adolescent Menstrual Cycle: A Systematic Literature Review - Syahla Rizki Alifiya; Nagita Vicilya Utami; Arih Diyaning Intiasari; Eri Wahyuningsih (Green Publisher Indonesia, 2025)
The menstrual cycle is the time between the beginning of menstruation in the previous period and the onset of the next period. One of the factors that affect the menstrual cycle is nutritional intake and nutritional status. This study aims to determine the importance of nutritional intake and nutritional status on the menstrual cycle in adolescents. This article uses a selection method based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) diagram, in accordance with the inclusion criteria and predetermined keywords, and identified 10 articles to be analyzed. Based on the 10 articles analyzed, it was found that most show the importance of nutritional intake and nutritional status in affecting the regularity of the menstrual cycle. Several articles also demonstrate a relationship between both micro and macro nutritional intake and nutritional status on the menstrual cycle in adolescent girls. Nutritional intake and nutritional status play an important role in the regularity of adolescent menstrual cycles. These findings have important implications for public health policy, suggesting the need for comprehensive nutritional education programs targeting adolescent girls, healthcare providers, and educators. The evidence supports the development of school-based nutrition interventions and clinical guidelines for managing menstrual irregularities through nutritional approaches. Moreover, there is a clear relationship between nutritional intake and nutritional status and the menstrual cycle.